Microdeletion at chromosome 4q21 defines a new emerging syndrome with marked growth restriction, mental retardation and absent or severely delayed speech. Issue 6 (3rd June 2010) - Bonnet, C; Andrieux, J; Béri-Dexheimer, M; Leheup, B; Boute, O; Manouvrier, S; Delobel, B; Copin, H; Receveur, A; Mathieu, M; Thiriez, G; Le Caignec, C; et al.
Abstract : Background: Genome-wide screening of large patient cohorts with mental retardation using microarray-based comparative genomic hybridisation (array-CGH) has recently led to identification several novel microdeletion and microduplication syndromes. Methods: Owing to the national array-CGH network funded by the French Ministry of Health, shared information about patients with rare disease helped to define critical intervals and evaluate their gene content, and finally determine the phenotypic consequences of genomic array findings. Results: In this study, nine unrelated patients with overlapping de novo interstitial microdeletions involving 4q21 are reported. Several major features are common to all patients, including neonatal muscular hypotonia, severe psychomotor retardation, marked progressive growth restriction, distinctive facial features and absent or severely delayed speech. The boundaries and the sizes of the nine deletions are different, but an overlapping region of 1.37 Mb is defined; this region contains five RefSeq genes: PRKG2, RASGEF1B, HNRNPD, HNRPDL and ENOPH1 . Discussion: Adding new individuals with similar clinical features and 4q21 deletion allowed us to reduce the critical genomic region encompassing two genes, PRKG2 and RASGEF1B . PRKG2 encodes cGMP - dependent protein kinase type II, which is expressed in brain and in cartilage. Information from genetically modified animal models is pertinent to the clinical phenotype. RASGEF1B is a guanine nucleotide exchange factor for Ras family proteins, and several members have been reported as key regulators of actin and microtubule dynamics during both dendrite and spine structural plasticity. Conclusion: Clinical and molecular delineation of 4q21 deletion supports a novel microdeletion syndrome and suggests a major contribution of PRKG2 and RASGEF1B haploinsufficiency to the core phenotype.